Screening of sugar tolerant fast growing lactic acid bacteria for preparation of misti dahi: Sugar tolerating lactic acid bacteria for misti dahi - Majumder, Reshab; Himanshu; Manorama Kumari; Shaik Abdul Hussain; Behare, Pradip Vishnu (Indian Journal of Dairy Science, 2024)
Misti dahi, a popular fermented milk product in eastern India, is experiencing growing demand across the country. To meet the increasing demand, it is essential to identify sugar-tolerant starter cultures that can ensure more desirable and consistent fermentation outcomes while minimizing the risk of fermentation failure. This study aimed to isolate, screen, and identify sugar-tolerant cultures suitable for misti dahi production. Out of ten isolated cultures, S. thermophilus MD3 exhibited remarkable tolerance to high sugar concentrations of up to 20% in milk without compromising cell viability and curdling time. Moreover, it consistently produced misti dahi of superior quality in terms of physicochemical, microbiological, textural, sensory, and rheological attributes. The isolated S. thermophilus MD3 culture holds potential for commercialization in misti dahi production.